Robotics and Mechatronics : Proceedings of the 6th IFToMM International Symposium on Robotics and Mechatronics (ISRM 2019) - International Symposium on Robotics and Mechatronics (6th : 2019); Kuo, Chin-Hsing, editor; Lin, Pei-Chun, editor; Essomba, Terence, editor; Chen, Guan-Chen, editor (Cham : Springer International Publishing : Imprint : Springer, 2020)
This book gathers the latest advances, innovations and applications in the field of robotics and mechatronics, as presented by leading international researchers and engineers at the 6th IFToMM International Symposium on Robotics and Mechatronics (ISRM), held in Taipei, Taiwan, on October 28-30, 2019. It covers highly diverse topics, including mechanism synthesis, analysis, and design, kinematics and dynamics of multibody systems, modelling and simulation, sensors and actuators, novel robotic systems, industrial- and service-related robotics and mechatronics, medical robotics, and historical developments in robotics and mechatronics. The contributions, which were selected through a rigorous international peer-review process, share exciting ideas that spur novel research directions and foster new, multidisciplinary collaborations